Clinical electroencephalogram (EEG) evaluation is improved by the amplitude asymmetry index - Luccas, Francisco José Carchedi; Bártolo, Thalita; Silva, Nayara Lucio da; Cavenaghi, Barbara (Arquivos de Neuro-Psiquiatria, 2016)
Cerebral hemispheres, although similar, are neither completely symmetrical in structure nor equivalent in function. EEG asymmetry studies have been directed more to frequency than to amplitude analysis. Objective Better definition of normal amplitude asymmetry values on the classical EEG frequency bands.Results EEG amplitude asymmetry index (AAI) is physiologically low in normal adults, differences usually lesser than 7%.Conclusion Persistent or intermittent amplitude asymmetry regional differences higher than 7% may be suggestive of pathology after adequate correlation with clinical data and EEG classical visual analysis.
Keywords: Electroencephalography; amplitude; asymmetry